PENGAWASAN MASYARAKAT PADA PENGELOLAAN BADAN USAHA MILIK DESA DI DESA GOSOMA KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA - BARUTI, VERENDITHA SEPTIANA; LONDA, VERY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2022)
Supervision is the most essential management function, no matter how good the work carried outwithout supervision cannot be said to be successful. Community supervision not only involves thecommunity in decision-making in every development program implemented by the goverment in thevillage, but the community is also involved in identifying problems and potentials that exist in thecommunity. Village Owned Enterprise (BUMDES) is a legal entity established by the village to managethe bussines, utilize asset, delevop village potential, and provide as many types of bussines as possiblefor the welfare of the village community. So this study uses a type of qualitative research where theresearch is descriptive, namely the collection of primary and secondary data conducted throughinterviews and then processed and obtained results. The result of the study show that the problems thathinder the not running of the BUMDES in Gosoma village are that supervision is not carried out by thecommunity but the village goverment, the community understands that they have no responsibility insupervision, village owned enterprise managers or administrators are irresponsible and the savings andloan work program is jammed. The selection of work programs that are not in accordance with the needsof the community has resulted in only part of the community being able to feel it.Keywords: Supervision, Management, Program